PENERAPAN MEDIA FOODCHAIN WHILE MATCHING CORRECT SEQUENCE UNTUK MENINGKATKAN PEMAHAMAN SISWA MENGENAI RANTAI MAKANAN EKOSISTEM KELAS V SD - Adinda Putri Darmanto; Pratiwi Kartika Sari; Bunga Seftya Nur Indah (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research was motivated by the low level of students’ understanding of the food chain ecosystem material in Grade V at SDN Pondok Cabe Ilir 01. This indicates the need for the implementation of learning media that can enhance student engagement in the learning process. The aim of this study is to improve students’ understanding through the use of the Food Chain While Matching Correct Sequence learning media. The type of research used is Classroom Action Research (CAR) with the Kemmis and McTaggart model design, which was carried out in two cycles. Each cycle consists of the stages of planning, action implementation, observation, and reflection. The subjects of this study were Grade V students of SDN Pondok Cabe Ilir 01. The data collection techniques used were observation and tests. The instruments used included observation sheets and psychomotor skill tests. The results showed a significant improvement in students’ understanding. The average student score increased to 79 in the first cycle, and 92.92 in the second cycle. The percentage of student learning mastery also increased from 31% in the pre-action stage to 69% in the first cycle, and reached 100% in the second cycle. Therefore, it can be concluded that the Food Chain While Matching Correct Sequence media is effective in improving the understanding of Grade V students on food chain material in science learning.